Assessment of Wavefront Aberrations in Children with Myopia Against the Background of Ocular Surface Disorders in Combination with Computer Vision Syndrome Digital and Eye Strain - I. L. Plisov; E. M. Naumova; A. I. Smoleva (Oftalʹmologiâ, 2024)
Purpose: to assess the state of the wavefront in children with myopia, who have various manifestations of digital eye strain and symptoms of ocular surface disorders, and to evaluate the diagnostic significance of wavefront criteria for assessing the state of the ocular surface.Patients and methods. The study involved 76 children (152 eyes) with myopia aged 8 to 18 years who used gadgets and computers for more than 2 hours a day. All patients used glasses as a method of optical correction and were constantly worn. The patients were divided into 2 groups: 1st with symptoms of ocular surface disorder, 2nd — comparison group. Subjective signs were studied using the online questionnaire “State of the ocular surface”. Using the “Keratograph 5M Oculus” the following parameters were assessed: noninvasive tear film breakup time (NTBR), including the first tear film breakup time, average tear film breakup time, breakup time gradient and maximum tear film breakup zone, the same device was used to perform infrared meibography and study of the lipid layer of the tear film. All patients underwent wavefront aberrometry in a darkened room without cycloplegia.Results. It was found that in the group of patients with the presence of subjective phenomena of disturbance of the state of the ocular surface, identified using the online questionnaire “State of the ocular surface”, rotor aberrations were statistically significantly higher than in the comparison group. At the same time, the indicators of higherorder corneal aberrations have comparable values. Correlation analysis between indicators of the state of the ocular surface and parameters of the wavefront in the group of children with disturbances of the state of the ocular surface showed that a higher level of corneal aberrations corresponds to a higher number of points on the questionnaire of disturbances of the ocular surface and the state of visual comfort, in turn, when comparing data on noninvasive tear film breakup time, a negative correlation was established, which means that with a higher number of points on the questionnaire, and therefore, with a more significant degree of impairment of the ocular surface, the tear film breakup time was shorter.Conclusion. The structure of the wavefront in children with myopia against the background of a disorder of the ocular surface in combination with CVS and digital eye strain is significantly different from the structure of the wavefront in the comparison group.